Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence 2018
DOI: 10.24963/ijcai.2018/30
|View full text |Cite
|
Sign up to set email alerts
|

Opinion Diffusion and Campaigning on Society Graphs

Abstract: We study the effects of campaigning, where the society is partitioned into voter clusters and a diffusion process propagates opinions in a network connecting those clusters. Our model is very general and can incorporate many campaigning actions, various partitions of the society into voter clusters, and very general diffusion processes. Perhaps surprisingly, we show that computing the cheapest campaign for rigging a given election can usually be done efficiently, even with arbitrarily-many voters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 33 publications
(72 reference statements)
0
29
0
Order By: Relevance
“…They have shown that the problem can be approximated within the same bound. A similar problem has been studied in [13]. The authors consider a network where each node is a set of voters with the same preference list, and edges connect nodes whose preference lists differ by the ordering of a single pair of adjacent candidates.…”
Section: Related Workmentioning
confidence: 99%
“…They have shown that the problem can be approximated within the same bound. A similar problem has been studied in [13]. The authors consider a network where each node is a set of voters with the same preference list, and edges connect nodes whose preference lists differ by the ordering of a single pair of adjacent candidates.…”
Section: Related Workmentioning
confidence: 99%
“…In both cases, the election control problem can be solved with an approximation factor of 1 3 (1 − 1/e) in the constructive scenario and 1 2 (1 − 1/e) in the destructive one. Moreover, Faliszewski et al [11] studied a variant of the Linear Threshold Model with weighted vertices; in their scenario, each node of the graph is a group of voters with a specific list of candidates and there is an edge between two nodes if they differ by the ordering of a single pair of adjacent candidates. Bredereck et al [12] instead focused on a simple Linear Threshold Model, where each node holds a binary opinion, each edge has the same fixed weight, and all vertices have a threshold fixed to 1/2; in this scenario, they studied how to manipulate, by means of bribing nodes or adding/deleting edges, the network in order to have control on the majority opinion, i.e., having more than 50% of nodes with the same opinion.…”
Section: Related Workmentioning
confidence: 99%
“…A number of recent works study social influence as a means of election control (Sina et al 2015;Faliszewski et al 2018;Wilder and Vorobeychik 2018;. The crucial difference in our model is that voters are strategic players, who update their beliefs rationally.…”
Section: Introductionmentioning
confidence: 99%